2022
DOI: 10.1098/rsos.220047
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown highlights impact of recreational activities on the behaviour of coral reef fishes

Abstract: In 2020, the COVID-19 pandemic led to a reduction in human activities and restriction of all but essential movement for much of the world's population. A large, but temporary, increase in air and water quality followed, and there have been several reports of animal populations moving into new areas. Extending on long-term monitoring efforts, we examined how coral reef fish populations were affected by the government-mandated lockdown across a series of Marine Protected Area (MPA) and non-Marine Protected Area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In addition, the period from May to August usually corresponds to the period of lowest sea surface temperatures in French Polynesia, when fishes are generally less abundant and larval recruitment is lower (Galzin 1987 ; Lo-Yat et al 2011 ). Therefore, the higher apparent density of fish observed in May, June and July 2020 compared to the overall 2019 average could be related to behavioural changes due to the lockdown period (similar to Feeney et al 2022 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, the period from May to August usually corresponds to the period of lowest sea surface temperatures in French Polynesia, when fishes are generally less abundant and larval recruitment is lower (Galzin 1987 ; Lo-Yat et al 2011 ). Therefore, the higher apparent density of fish observed in May, June and July 2020 compared to the overall 2019 average could be related to behavioural changes due to the lockdown period (similar to Feeney et al 2022 ).…”
Section: Discussionsupporting
confidence: 55%
“…However, despite the inability to statistically compare the relationship between fish density and nautical/fishing activities on the three coastline habitats, we can postulate that any change in the fish community would mainly depend on the degree of human activity existing at the location ordinarily and the intensity of the change after the lockdown, as this has been suggested by other recent studies (e.g. Edward et al 2021 ; Lecchini et al 2021 ; Feeney et al 2022 ). Furthermore, at Moorea, we are not aware of any particular variations or events (potentially related to weather, cyclone, coral bleaching or environmental conditions) that may have occurred during the same period that could explain the observed changes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, it is possible that the prolonged lockdown at Lizard Island led to a general increase in fish density due to the large reduction in human activities. Recent studies have shown a significant increase in coral reef fish densities during the lockdown period (Feeney et al, 2022; Bertucci et al, 2023). However, it is also possible that the lockdown affected the fish assemblage, which resulted in higher numbers during surveys, but this could lead to a decline in fish numbers once the lockdown is lifted and human activities resume (Lecchini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pollution in the form of anthropogenic noise and chemical pollution from sea vessels negatively impacts fish behaviour 31 33 and physiology 31 , 33 , 34 thereby influencing community composition. During the short period when tourism and heavy water-based activities were reduced between March and May 2020, coral reef ecosystems in several regions that typically experience high anthropogenetic pressures showed immediate increases in fish species diversity and abundance 35 37 , linked to increased recruitment of juvenile fishes 38 . While marked increases immediately following a short respite is positive, studies examining how longer lockdown restrictions on water-based activities influenced the community composition are lacking.…”
Section: Introductionmentioning
confidence: 99%